Development disrupted : the global South in the twenty-first century - Gordon, Ruth Elizabeth (Cambridge : Cambridge University Press, 2022)
Although the impact of rapid technological change is often discussed in relation to the Global North, this book explores its effects on the development of the Global South. By tracing the discourse and practice of international development in the twentieth century, Ruth E. Gordon offers necessary context to current changes in the global hierarchy. The book explores the situation of the Global South within the international legal, political, and economic order, how current development discourse and practice engages modernization efforts, and how technology can bring about significant economic and societal change for middle and low-income nations. It offers a balanced account of the positive and negative impacts of technological change on the Global South, from mobile phones allowing access to knowledge to robotics reducing employment opportunities. This book demonstrates that, for the Global South, technology is making more things both conceivable and achievable.
Title from publisher's bibliographic system (viewed on 25 Jul 2022).
Keywords: Economic development -- Developing countries